Influence of ion mobility and electrode structure effects on supercapacitors with CaO, MgO, and SiO2 - Yargi, Onder; Bostanci, Eda; Filiz, Bilge Coskuner; Figen, Aysel Kanturk (SPRINGER HEIDELBERG, 2025)
Supercapacitors, utilizing advanced technology for energy storage, offer high power density and rapid charging capabilities. However, using pure calcium oxide (CaO), magnesium oxide (MgO), and silicon dioxide (SiO2) in supercapacitors presents several challenges. CaO easily absorbs moisture from the air, turning into Ca(OH)(2), which weakens its performance, and its poor conductivity and brittleness complicate its use. MgO also has low conductivity and surface area, limiting its effectiveness, and it reacts with moisture and carbon dioxide, degrading over time. SiO2, being an insulator, does not conduct electricity and needs to be combined with conductive materials, which complicates its use. Additionally, SiO2 is brittle and can develop cracks during repeated charging cycles, and combining it with other materials can be tricky due to compatibility issues. This study investigates novel approaches to enhance supercapacitor performance by examining the electrochemical properties of CaO, MgO, SiO2, and their composites with reduced graphene oxide (rGO) solutions. The novelty of this study lies in tackling the challenges of using CaO, MgO, and SiO2 in supercapacitors by creating composites with reduced graphene oxide (rGO). This approach significantly improves the conductivity and stability of these materials. Specifically, the combination of CaO with rGO shows remarkable results, achieving a high specific capacitance of 113 F/g and retaining 99% of its capacitance even after 2000 cycles. This innovative method addresses the poor performance and stability issues of pure metal oxides, leading to better charge storage and durability in supercapacitors. The study employs electrochemical analyses and advanced microscopy techniques to characterize the composite electrodes and understand their structural and functional properties in depth. Employing a two-electrode setup with porous nickel foam substrates and a lithium perchlorate (LiClO4) electrolyte, we conducted comprehensive electrochemical analyses, including cyclic voltammetry (CV) and galvanostatic charge and discharge (GCD) techniques. Additionally, X-ray photoelectron spectroscopy (XPS) and scanning electron microscope (FESEM) analyses were utilized to characterize the crystal structure and morphology of the electrodes.
Keywords: Ion mobility; Electrode structure; Supercapacitors; MANGANESE OXIDE; FILMS; COMPOSITES; CARBON; SIZE; Chemistry; Electrochemistry; Physics